2019
DOI: 10.1063/1.5116325
|View full text |Cite
|
Sign up to set email alerts
|

Twist-angle modulation of exciton absorption in MoS2/graphene heterojunctions

Abstract: The twist-angle dependence of exciton absorption in a molybdenum disulfide (MoS2)/graphene heterostructure (MGH) is reported. Using photoluminescence (PL) spectroscopy, we found that, as the twist angle increased, the MGH demonstrated an enhancement of PL intensity and a peak position blueshift, indicating that the exciton radiative recombination was positively correlated with the twist angle. In addition, optical reflectance measurements were performed in order to investigate the exciton absorption in the MGH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…Correspondingly, the exciton formation process was promoted to facilitate exciton absorption, owing to the decreasing interlayer electron transfer (Figure 14e), where a wavelength of 620 nm corresponded to the photoluminescence peak of MoS 2 . [29] Additionally, the exciton lifetimes also exhibited a significant difference when the stacking order of graphene and TMDCs was varied. From transient absorption spectroscopy, the exciton lifetime of the WSe 2 /graphene heterostructure (Figure 14f) was considerably higher than that of the graphene/WSe 2 heterostructure (Figure 14g), owing to the difference in charge screening of the substrate.…”
Section: Excitonsmentioning
confidence: 99%
See 3 more Smart Citations
“…Correspondingly, the exciton formation process was promoted to facilitate exciton absorption, owing to the decreasing interlayer electron transfer (Figure 14e), where a wavelength of 620 nm corresponded to the photoluminescence peak of MoS 2 . [29] Additionally, the exciton lifetimes also exhibited a significant difference when the stacking order of graphene and TMDCs was varied. From transient absorption spectroscopy, the exciton lifetime of the WSe 2 /graphene heterostructure (Figure 14f) was considerably higher than that of the graphene/WSe 2 heterostructure (Figure 14g), owing to the difference in charge screening of the substrate.…”
Section: Excitonsmentioning
confidence: 99%
“…[ 185 ] Moreover, the exciton effect also appeared in the graphene/TMDCs, such as graphene/MoS 2 , which showed that the exciton absorption is dependent on the twist angle. [ 29 ] As the twist angle increased, the interlayer coupling declined. Correspondingly, the exciton formation process was promoted to facilitate exciton absorption, owing to the decreasing interlayer electron transfer (Figure 14e ), where a wavelength of 620 nm corresponded to the photoluminescence peak of MoS 2 .…”
Section: Correlated Physical Performances In Graphene‐based Moiré Heterostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…[109,110] De fato, observa-se que heterojunções formadas por MoS 2 /Gr com band-gap na região do espectro visível apresentam grande condutividade eletrônica, candidatando estes materiais híbridos para o uso em dispositivos fotovoltaicos. [111,112] Ademais, heterojunções MoS 2 /Gr encontram usos em sensores, [113,114] além do fato que a variação de hibridizações relativas, de acordo com o ângulo de rotação entre as monocamadas, produzirem comportamentos condutivos específicos (área que é conhecida como twistronics). [115,116] Os métodos mais utilizados atualmente para a síntese de heteroestruturas verticais MoS 2 /Gr, como a CVD, provêm materiais de alta qualidade e escaláveis.…”
Section: Nanoflocos De Dicalcogenetos De Metais De Transição Adsorvidunclassified